Identification of diverse activating mutations of the RAS-MAPK pathway in histiocytic sarcoma - Shanmugam, Vignesh; Griffin, Gabriel K.; Jacobsen, Eric D.; Fletcher, Christopher D. M.; Sholl, Lynette M.; Hornick, Jason L. (Modern pathology, 2019)
Recent studies have demonstrated recurrent activating mutations involving the classical MAPK and PI3K signaling pathways in a large proportion of histiocytic neoplasms, such as Langerhans cell histiocytosis. However, very little is known about the molecular genetics of histiocytic sarcoma, a rare aggressive malignant neoplasm that shows pathologic characteristics of mature macrophages. Here we report the genomic characteristics of a large cohort of histiocytic sarcomas ( n = 28) using a targeted next-generation sequencing approach to identify driver alterations. We identified recurrent mutations involving the RAS-MAPK signaling pathway ( MAP2K1 , KRAS , NRAS , BRAF , PTPN11 , NF1 , CBL ) in a majority (57%) of histiocytic sarcoma cases and report a clinical response to a MEK inhibitor (Cobimetinib) in a patient with a NF1 -mutated histiocytic sarcoma. A smaller subset of cases (21%) also showed mutations resulting in activation of the PI3K signaling pathway ( PTEN , MTOR , PIK3R1 , PIK3CA ). In addition, the tumor-suppressor gene CDKN2A was the most frequently altered gene (46%). Further, a subset of histiocytic sarcoma cases shows striking molecular genetic similarities to B cell lymphomas, supporting a clonal relationship between B cell neoplasms and a subset of histiocytic sarcomas. These findings support a cooperative role for MAPK, PI3K, and cyclin-CDK4/6-INK4 signaling in the pathogenesis of histiocytic sarcoma and provide a rational basis for targeting these pathways.